2020
DOI: 10.1002/acm2.12814
|View full text |Cite
|
Sign up to set email alerts
|

Method of determining geometric patient size surrogates using localizer images in CT

Abstract: Purpose Size‐specific dose estimates (SSDE) requires accurate estimates of patient size surrogates. AAPM Report 204 shows that the SSDE is the product of CTDIvol and a scaling factor, the normalized dose coefficient (NDC) which depends on patient size surrogates for CT axial images. However, SSDE can be determined from CT localizer prior to CT scanning. AAPM Report 220 charges that a magnification correction is needed for geometric patient size‐surrogates. In this study, we demonstrate a novel “model‐based” ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Anam et al reported 5.4 ± 4.2 % and 2.3 ± 3.2 % errors in calculating T W in an anthropomorphic phantom study and 30 clinical cases, respectively [10]. Our results showed similar R 2 achieved by the proposed metric compared to Burton et al [24], wherein they used both AP and lateral images simultaneously. We only used a single AP localizer commonly acquired in clinical protocols.…”
Section: Dice-s Dw-e-s(%) Dw-e-t(%) Dw-abs-e-t(%)supporting
confidence: 72%
See 1 more Smart Citation
“…Anam et al reported 5.4 ± 4.2 % and 2.3 ± 3.2 % errors in calculating T W in an anthropomorphic phantom study and 30 clinical cases, respectively [10]. Our results showed similar R 2 achieved by the proposed metric compared to Burton et al [24], wherein they used both AP and lateral images simultaneously. We only used a single AP localizer commonly acquired in clinical protocols.…”
Section: Dice-s Dw-e-s(%) Dw-e-t(%) Dw-abs-e-t(%)supporting
confidence: 72%
“…They validated their model on body CTDI phantom, an anthropomorphic phantom, and 30 clinical studies, reporting an average error in DW calculation of 5.4 ± 4.2 % compared with axial images serving as ground truth (GT). Burton et al [24] reported a good agreement between size metrics estimated from two AP and lateral images and the metrics measured from axial CT images on 284 chest CT images with R 2 = 0.92. Terashima et al [20] evaluated the effect of TH on the accuracy of DW estimates from the AP localizer and found a suitable CF based on TH with an error equal to 2.4 % in an anthropomorphic phantom study.…”
Section: Introductionmentioning
confidence: 90%
“…According to the AAPM TG Report 220, using the water-equivalent diameter (WED) is the "preferred" method in determining the SSDE because it factors in patient attenuation properties. Burton and Szczykutowicz 9 demonstrated that calculating patient size surrogates such as WED from patient data was similar to the results of the AAPM TG Reports 204 and 220, 10 thus providing the medical imaging community with a gold standard for calculating WED from patient data. Zhang et al determined a calibration method that may be used to determine the WED from CT localizers using phantoms, 11 however it has not been extended to patient scans.…”
Section: Introductionmentioning
confidence: 72%
“…Estimating WED from CT localizer radiographs would allow for WED to be included into data-driven clinical workflows such as size adaptive protocol selection using diagnostic reference ranges which provide a minimum estimated patient dose. 17,18 The additional benefits of using CT localizers include reduced data overhead if CT axial images are not stored and possible limitations such as couch removal 10,19 related to CT axial calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the localizer-based patient size estimation, especially with localizer in the AP or PA directions, is subject to errors resulted from magnification or minification, and proposed various correction schemes to address these errors. 2,18,[27][28][29] In our study, we intentionally only tested lateral localizers and ensured that the phantoms were imaged at the isocenter of the scanners. With these setups, the impact of magnification or minification was minimized.…”
Section: Discussionmentioning
confidence: 99%